1960
DOI: 10.1021/jf60110a008
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Measurement, Determination of Toxaphene by a Spectrophotometric Diphenylamine Procedure

Abstract: A confirmatory method for the positive identification of toxaphene in small residues has not previously been reported. A sensitive method for the qualitative and quantitative determination of toxaphene in residues and in formulations is based on fusion with diphenylamine in the presence of zinc chloride. The greenish blue reaction product, dissolved in acetone or glacial acetic acid, has an absorbance maximum at 640 mp. Toxaphene in the range of 20 to 700 y can be readily determined b y spectrophotometric meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1960
1960
1979
1979

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…All samples were analyzed by the colorimetric diphenylamine procedure for toxaphene (4), with minor modifications. Chromatographic columns used for cleanup were 19 mm.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were analyzed by the colorimetric diphenylamine procedure for toxaphene (4), with minor modifications. Chromatographic columns used for cleanup were 19 mm.…”
Section: Methodsmentioning
confidence: 99%
“…McKinley and Graham (12) used diphenylamine-ZnCl 2 to identify captan on paper chromatograms. Cueto (13) employed this reagent for the colorimetric determination of dieldrin, and Graupner and Dunn (14) used it for the colorimetric determination of toxaphene. These authors also reported on colors given by pesticides other than those for which they developed methods.…”
Section: Diphenylamine-zinc Chloride As a Chromogenic Agent For The Dmentioning
confidence: 99%
“…The objective of the present study was to find the chromogenic agent that would best distinguish toxaphene, DDT, and chlordane in combination when they are chromato-graphed on thin layer plates. The literature cited above (11)(12)(13)(14) showed that diphenylamine-ZnCl 2 gave various colors with a number of chlorinated pesticides; therefore, this reagent was investigated. The results reported here were obtained by applying diphenylamine-ZnCl 2 to chlorinated pesticides on Al 2 0 a plates.…”
Section: Diphenylamine-zinc Chloride As a Chromogenic Agent For The Dmentioning
confidence: 99%
“…Graupner and Dunn (21) have reported a method for determining residues of toxaphene by means of fusion with diphenylamine in the presence of zinc chloride. The reaction product from the fusion was dissolved in acetone or glacial acetic acid and determined spectrophotometrically.…”
Section: Chlorinated Hydrocarbonsmentioning
confidence: 99%